Efektivitas Konsultan Pajak Dalam Meningkatkan Kepatuhan Wajib Pajak Pada UMKM - Liberti, Corline Ajeng; Anjelina, Septina; Hasanah, Uswatun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Taxpayer compliance is one of the keys to success in optimizing state revenues originating from taxes. However, the Micro, Small and Medium Enterprises (MSME) sector often experiences problems in fulfilling tax obligations. Barriers such as low understanding of tax regulations, limited resources, and minimal access to information cause the level of MSME compliance with taxes to be relatively low. This research aims to explore the role of tax consultants in increasing MSME taxpayer compliance and identify factors that influence their effectiveness. The research method uses a qualitative approach with data collection techniques in the form of in-depth interviews, observation and document analysis. The research results show that tax consultants contribute significantly to increasing compliance through education, administrative assistance and strategic consultation. However, the effectiveness of this service is influenced by cost factors, regulatory complexity, and the accessibility of consulting services. Therefore, policies are needed that support the continued access of MSMEs to tax consultant services, including subsidies and simplification of tax regulations.